Choosing Optimal Reliability Measures for Passenger Railways: Different Measures for Different Purposes - Karathodorou,N; Condry,BJ (Transportation Research Record, 2016)
Reliability is one of the top factors influencing customer satisfaction with passenger rail services. It affects the level of demand for the service as passengers place a large negative value on delays. This matters to service providers, as it drives the fare revenue, and to policy makers as it influences mode share. This paper comprises a review of literature on reliability measurement in public transport, the results of a global survey of suburban rail operators and an assessment of the value of specific reliability measures. Reliability measures are typically required for three distinct purposes: internal measurements to manage the service, reporting to governments/authorities or franchisors for regulatory purposes and external reporting to customers and the media. Different measures may be optimal for each of these purposes and careful consideration is required for their definition and use. However, most railways surveyed chose their reliability measures either based on regulatory obligations or simply because these were used elsewhere.